Identifying Organizational Factors Effective Knowledge Concealment in Scientific Contexts (Case Study: Islamic Azad University of Khorasan Razavi) - Hoseinpour, Mahdi; Salajghe, Sanjar; Jalal Kamali, Mohammad (Journal of Information and Organizational Sciences, 2022)
This study aims to investigate the organizational factors affecting knowledge concealment in scientific contexts. This study has taken a mixed approach to identify these factors, so what makes it unique is the pluralism of data collection methods. Also, using the "Delphi" method, a conceptual model of organizational factors affecting knowledge concealment in scientific contexts is presented. The statistical sample included 314 employees of the Islamic Azad University of Khorasan Razavi who were selected through the random sampling method. They filled knowledge concealment questionnaire by Demirkasimoglu (2016) and a scholar-made questionnaire. Data were analyzed using the structural equation method (SEM) in AMOS software. Findings revealed that the coefficient correlation of organizational culture, reward system, organizational structure, organizational support, organizational justice, quality of work-life, and leadership style with knowledge concealment was -0.62, -0.27, -0.49, -1.30, -0.77, -0.39, and -0.88, respectively. The results indicate that organizational factors have an inverse and significant relationship with knowledge concealment.